PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS MENGGUNAKAN MODEL KOOPERATIF MAKE A MATCH DI SD - Azhary, Abang; Asran, Mastar; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe purpose of this study is to determine the increase in activity and learning outcomes of students on learning Social Sciences using the Model Make A Match cooperative in class 3B Elementary School 16 Pontianak North. The method used in this research is descriptive method, the form of research that is action research class. The subjects of the study were students of class 3B, which amounted to 34 people. The result of capability of learning plan in cycle I is 3.41. In the average cycle II increased to 3.86. The ability of teachers to implement the average learning cycle I is 3.40. In cycle II average 3.86. Student learning activity in cycle I is 62,94%. In the second cycle increased to 80.29%. Student learning outcomes cycle I average 77.94 and on the second cycle rose to 87.65. From the result of the research, it can be concluded that there is an increase of activity and student learning outcomes by using the Make A Match cooperative model in Grade 3B State Elementary School 16 Pontianak northÂ Keywords: Activity, Learning Outcomes, Make A Match